Virtual Tai Chi program for patients with irritable bowel syndrome with constipation: Proof-of-concept feasibility trial - Staller, Kyle; Paz, Mary; Rones, Ramel; Macklin, Eric A.; Garcia-Fischer, Isabelle; Murray, Helen Burton; Kuo, Braden (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details